Echocardiography in mitral stenosis - Omran, A.S. (2010)
Echocardiography plays a major role in diagnosis, etiology and severity of Mitral Stenosis (MS), analysis of valve anatomy and decision-making for intervention. This technique has also a crucial role to assess consequences of MS and follow up of patients after medical or surgical intervention. In this article we review the role of conventional echocardiography in assessment of mitral stenosis and future direction of this modality using 3D echocardiography.